Inflamatory Pseudotumor of the Bladder: A Histopathological Diagnostic Challenge from Its Malignant Variant. - Muhammad Akbar; S, Praveen; HCK, Christopher; EH, Goh; Swaminathan; Zulkifli MZ (Department of Surgery, UKM Medical Centre, 2012)
Inflammatory Pseudotumor (IP) of bladder is one of a variety of lesions which may arise from spindle cell lesions in the bladder. It is benign in nature compared to the other end of the spectrum of spindle cell lesions, such as sarcoma, sarcomatoid carcinoma and leiomyosarcoma. The diagnosis of IP and its differentiation from a malignant pathology is a diagnostic dilemma for Urologist and Pathologist as both entities share certain similar morphological and histo-pathological appearance as well as immuno-histo chemistry staining. It is however crucial to avoid misdiagnosis as the treatment option varies significantly between a radical or partial cystectomy with future surveillance cystoscopes. Hereby, we highlight a case of a benign variant of spindle cell tumour of bladder which needed second pathology review for confirmation and thus avoiding a radical cystectomy. We also review the literature on its presentation and emphasis characteristics differentiating a benign from a malignant pathology.